2016
DOI: 10.1103/physrevlett.117.077003
|View full text |Cite
|
Sign up to set email alerts
|

HighTcvia Spin Fluctuations from Incipient Bands: Application to Monolayers and Intercalates of FeSe

Abstract: We investigate superconductivity in a two-band system with an electronlike and a holelike band, where one of the bands is away from the Fermi level (or "incipient"). We argue that the incipient band contributes significantly to spin-fluctuation pairing in the strong coupling limit where the system is close to a magnetic instability and can lead to a large T_{c}. In this case, T_{c} is limited by a competition between the frequency range of the coupling (set by an isolated paramagnon) and the coupling strength … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
57
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(66 citation statements)
references
References 41 publications
(49 reference statements)
6
57
3
Order By: Relevance
“…In stark contrast to previous proposals, our here predicted deep Fermi sea Cooper pairing does not depend upon interband scattering processes mediated by bosons at large wavevectors, like e.g. antiferromagnetic spin fluctuations [27,28] or the conventional short-ranged in real space EPI [29].In the presence of a strong inhomogeneous dielectric background, the EPI develops a pronounced forward scattering peak [18,30]. Here, the interface-induced EPI is modelled by a dispersionless mode at Ω=81 meV [21] coupled to FeSe electrons via the functional form g(q) = g 0 exp (−|q|/q c ) with q c = 0.3a −1 [6], with a the FeSe lattice constant.…”
contrasting
confidence: 99%
See 1 more Smart Citation
“…In stark contrast to previous proposals, our here predicted deep Fermi sea Cooper pairing does not depend upon interband scattering processes mediated by bosons at large wavevectors, like e.g. antiferromagnetic spin fluctuations [27,28] or the conventional short-ranged in real space EPI [29].In the presence of a strong inhomogeneous dielectric background, the EPI develops a pronounced forward scattering peak [18,30]. Here, the interface-induced EPI is modelled by a dispersionless mode at Ω=81 meV [21] coupled to FeSe electrons via the functional form g(q) = g 0 exp (−|q|/q c ) with q c = 0.3a −1 [6], with a the FeSe lattice constant.…”
contrasting
confidence: 99%
“…In stark contrast to previous proposals, our here predicted deep Fermi sea Cooper pairing does not depend upon interband scattering processes mediated by bosons at large wavevectors, like e.g. antiferromagnetic spin fluctuations [27,28] or the conventional short-ranged in real space EPI [29].…”
contrasting
confidence: 99%
“…1. In principle, the incipient electron band can still play a role in interband interactions and pair-breaking scattering, but these effects are not qualitatively relevant here because superconductivity is supported by robust bands at the Fermi level ( 32 , 33 ). We also discuss the possibility of a crossover from s to d symmetry with increasing x and conclude that this is very unlikely, in line with ARPES studies that find accidental nodes on hole bands all the way up to x = 1 ( 11 , 34 ).…”
Section: Introductionmentioning
confidence: 99%
“…In multiband systems, however, Fermi surface based interactions can stabilize pairing, in which case incipient bands may strongly enhance pairing, and exhibit large gaps [16]. In addition, it has recently been shown that even without such robust Fermi surface-based interactions, interband interactions with the incipient band alone can create high-T c superconductivity if one is close to a magnetic instability [17,18].…”
mentioning
confidence: 99%